Financial Literacy Series: Protect Your Family from Online Gambling - Kartawinata, Budi Rustandi; Syarifuddin, Syarifuddin; Kuswanto, Arif; Wardhana, Aditya (Journal of Digital Community Services, 2025)
The community service initiative in Bandung City sought to alleviate the adverse effects of internet gambling on families, specifically targeting stakeholders at Taman Indria Kindergarten, including educators and parents. The program aimed to equip participants with the knowledge and resources to safeguard families against the widespread dangers of online gambling. The program employed workshops and instructional sessions to promote active participation, allowing attendees to recognize indicators of gambling addiction, improve financial literacy, and obtain assistance options. The study indicated a significant enhancement in participants' comprehension of family protection, with 88% exhibiting heightened awareness after the sessions. The report underscores the significant impacts of online gambling, encompassing financial instability, interpersonal disputes, and adverse effects on children. It underscores a comprehensive strategy to address these challenges, including financial literacy, enhanced controls on gambling platforms, and integrated support services for impacted families. The program's success was apparent in cultivating a cooperative atmosphere among schools, parents, and the community, thereby establishing a safer and healthier environment for children. This effort corresponds with Sustainable Development Goals (SDG #3), fostering well-being and resilience in communities. This project emphasizes the significance of collective action in protecting family welfare and future generations by tackling the root causes of online gambling addiction and empowering families via education and community assistance.